Childhood obesity: implications for future health - Katzmarzyk, Peter T. (Henry Stewart Talks, 2010)
Identification of obese children, Factors associated with childhood obesity, Obesity and health in childhood, Childhood obesity and future health, Clinical implications of childhood obesity